Psychoanalytic Theory used in English Literature: A Descriptive Study (Global Journal of Human-Social Science, 2017)
Psychoanalysis is one of the modern theories that are used in English literature It is a theory that is regarded as a theory of personality organization and the dynamics of personality that guides psychoanalysis It is known that the closet connection between literature and psychoanalysis has always been deployed by the academic field of literary criticism or literary theory Among the critical approaches to literature the psychoanalysis has been one of the most controversial and for many readers the least appreciated In spite of that it has been regarded one of the fascinating and rewarding approach in the application of interpretative analysis This psychological interpretation has become one of the mechanisms to find out the hidden meaning of a literary text It also helps to explore the innate conglomerate of the writer s personality as factors that contribute to his experience from birth to the period of writing a book The goal of psychoanalysis was to show that behaviour which was caused by the interaction between unconscious and unconsciousness The proposed work titled Psychoanalytic theory used in English Literature A Descriptive Study aims to explore where psychoanalysis has been used by the author s in his her literary works in English literature This article also discusses the different psychoanalytic theory which was born out of the self-analysis under taken by Sigmund Freud in 1897
Keywords: psychoanalysis; oedipus complex; consciousness; literature; unconsciousness; daydream